Polymers in disordered environments - Fricke, Niklas; Sturm, Sebastian; Lämmel, Marc; Schöbl, Sebastian; Kroy, Klaus; Janke, Wolfhard (Diffusion Fundamentals, 2015)
Using a combination of analytical theory and newly developed numerical algorithms, we analyze the most pertinent conformational characteristics of three paradigmatic types of polymers in disordered environments: (i) flexible polymers in quenched, self-similar disorder as represented by a self-avoiding random walk on a critical percolation cluster, (ii) semiflexible polymers in quenched, steric disorder as represented by an equilibrium hard-disk fluid and (iii) semiflexible polymers subject to the random energy landscape that emerges from a surrounding network of similar semiflexible polymers.